‘If You Can’t Say Something Nice, Don’t Say Anything at All’: Coping with Interpersonal Tensions in the Parent-child Relationship during Adulthood - Birditt, Kira S. (2009)
Tensions are normative in the parent-child tie, but there is less information on the strategies used to cope with such tensions. This study examined strategies parents and adult children use in reaction to interpersonal tensions and the implications of those strategies for relationship quality. Parents and their adult sons and daughters (aged 22 to 49; N = 158 families, 474 individuals) reported the strategies they used in response to tensions with one another (constructive, destructive, and avoidant). Across dyads, parents and adult children reported using constructive strategies more often than destructive or avoidant strategies. Strategy use varied between and within dyads by generation, gender of parent, ethnicity, education, and age of child. Constructive strategies predicted better relationship quality, whereas avoidant and destructive strategies predicted poorer relationship quality. Parents may be more likely to use constructive strategies, which are meant to maintain the relationship due to their greater investment in the tie.